2008
DOI: 10.1111/j.1743-6109.2008.00885.x
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Psychological and Oral Medical Treatment Compared to Psychological Treatment Alone for ED

Abstract: Introduction Sexual function through pregnancy and the postpartum period is an important aspect of quality of life. Despite this, prospective studies are limited, and the impact of body image on sexual function has not been explored. Aims The current study reports on a pilot study that evaluated the effectiveness of a combined Internet-based psychological treatment program and oral medication compared to an Internet-based psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
0
17
1
Order By: Relevance
“…Previous research had clearly demonstrated that ED has an impact on the female partner [18] and that the overall quality of life of female partners improves when the ED is treated [5]. These findings would suggest that whether the treatment regime is principally medical [2] or psychological [19], it is more likely to be effective if the partner is involved in the treatment process. The findings clearly highlight the importance of a multidisciplinary approach to the treatment of sexual dysfunction [20].…”
Section: Discussionmentioning
confidence: 96%
“…Previous research had clearly demonstrated that ED has an impact on the female partner [18] and that the overall quality of life of female partners improves when the ED is treated [5]. These findings would suggest that whether the treatment regime is principally medical [2] or psychological [19], it is more likely to be effective if the partner is involved in the treatment process. The findings clearly highlight the importance of a multidisciplinary approach to the treatment of sexual dysfunction [20].…”
Section: Discussionmentioning
confidence: 96%
“…Gains during the therapy period were shown to be largely maintained at follow-up. Probably reporting on the same study sample, McCabe and Price reported that participants who received Internet therapy combined with medication reported similar results as participants who received Internet therapy alone [14].…”
Section: Introductionmentioning
confidence: 84%
“…Web-based interventions for psychological conditions have been found to have a moderate to large effect size [1,2] that is comparable to face-to-face interventions [3-5]. However, in a review of Web-based interventions, the median proportion of users completing all modules in a trial was 56% [6].…”
Section: Introductionmentioning
confidence: 99%